2010
DOI: 10.1037/a0018974
|View full text |Cite
|
Sign up to set email alerts
|

Parental reactions to children’s negative emotions: Prospective relations to Chinese children’s psychological adjustment.

Abstract: The prospective relations between five types of parental reactions to children's negative emotions (PRCNE) and children's psychological adjustment (behavioral problems and social competence) were examined in a two-wave longitudinal study of 425 school-age children in China. Parents (mostly mothers) reported their own PRCNE. Parents, teachers, and children or peers reported on children's adjustment. Parental punitive reactions positively predicted externalizing problems (controlling for baseline), whereas emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
96
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 45 publications
14
96
3
6
Order By: Relevance
“…Further inconsistencies were apparent in the results of the questionnaire compared with interview findings of the study by Scott et al (2010) in terms of the relationship between prosocial behaviours and positive parenting. Such discrepancies have been previously noted in the literature; for example in the study by Tao et al (2010), it was noticed that the relationship between authoritarian parenting styles and externalising problems was stronger using parental rather www.ccsenet.org/ass Asian Social Science Vol. 11, No.…”
Section: Discussionmentioning
confidence: 59%
“…Further inconsistencies were apparent in the results of the questionnaire compared with interview findings of the study by Scott et al (2010) in terms of the relationship between prosocial behaviours and positive parenting. Such discrepancies have been previously noted in the literature; for example in the study by Tao et al (2010), it was noticed that the relationship between authoritarian parenting styles and externalising problems was stronger using parental rather www.ccsenet.org/ass Asian Social Science Vol. 11, No.…”
Section: Discussionmentioning
confidence: 59%
“…The items are rated on a 4-point scale (1 ϭ really false to 4 ϭ really true). In a study of native Chinese children (Tao et al, 2010), the Chinese language version of this measure has demonstrated satisfactory internal reliabilities (␣s Ն .63), and parents' and teachers' ratings on this measure were correlated with measures of parenting practices and children's temperament. In this present sample, parents' and teachers' reports showed satisfactory alpha reliabilities (.69 and .86) and were positively correlated with each other (r ϭ .19, p ϭ .007).…”
Section: Measures Family Demographics and Migration History (Parent Rmentioning
confidence: 99%
“…Liu et al, 1999;X. Liu, Sun, Uchiyama, Li, & Okawa, 2000;Tao, Zhou, & Wang, 2010;Zhou et al, 2008). An earlier version of the CBCL has also been used with Chinese American parents (Huntsinger, Jose, & Larson, 1998).…”
Section: Measures Family Demographics and Migration History (Parent Rmentioning
confidence: 99%
“…(CECCONELLO et al, 2003;OTTO;SMITH, 1980;WEBER et al, 2002). Dentre as diversas formas de disciplina, a punição física é um método comum de disciplina utilizado pelos pais e sua utilização esta vinculada a afastar as crianças do mau caminho e mantê-las sobre a orientação e obediência dos pais (WEBER et al, 2002 PICCININI, 2001;AUCOIN et al, 2006;CECCONELLO et al, 2003;OTTO;SMITH, 1980;TAO et al, 2010;WEBER et al, 2002 Quanto aos estudos comparativos entre grupos culturais distintos, a constatação de que o estilo autoritário e a punição física como prática educativa são percebidos em maior proporção em afro-descendentes comparativamente com caucasianos e hispânicos coincide com o achado de outros estudos (COLMAN et al, 2006;SIMONS et al, 2007).…”
Section: Discussionunclassified
“…As práticas parentais são um caminho para desenvolver o medo através da informação verbal. , 2007;GAMBLE et al, 2007;TAO et al, 2010).…”
Section: Conceituação Teóricaunclassified